MICROTUBULE DISRUPTORS AND THEIR INTERACTION WITH BIOTRANSFORMATION ENZYMES - Modriansky, Martin; Dvorak, Zdenek (Biomedical papers, 2005)
Microtubule disruptors, widely known as antimitotics, have broad applications in human medicine, especially as anti-neoplastic agents. They are subject to biotransformation within human body frequently involving cytochromes P450. Therefore antimitotics are potential culprits of drug-drug interactions on the level of activity as well as expression of cytochromes P450. This review discusses the effects of four well-known natural antimitotics: colchicine, taxol (paclitaxel), vincristine, and vinblastine, and a synthetic microtubule disruptor nocodazole on transcriptional activity of glucocorticoid and aryl hydrocarbon receptors. It appears that microtubules disarray restricts the signaling by these two nuclear receptors regardless of cell cycle phase. Consequently, intact microtubules play an important role in the regulation of expression of cytochromes P450, which are under direct or indirect control of the two nuclear receptors.
Keywords: Antimitotic drugs/Drug metabolism/Cytochromes P450/Nuclear receptors/Gene expression